Development of an online solid-phase extraction with liquid chromatography method based on polymer monoliths for the determination of dopamine - Janků, Simona; Komendová, Martina; Urban, Jiří (Wiley-VCH, 2016)
Porous polymer monoliths have been used to develop an online solid-phase extraction with liquid chromatography method for determination of dopamine in urine as well as for a continuous monitoring of dopamine in flowing system. A polymerization mixture containing 4-vinylphenylboronic acid monomer has been used to prepare a trapping column based on specific ring formation reaction with dopamine cis-diol functionality. Additionally, a monolithic stationary phase with zwitterion functionality has been used to prepare capillary column for the separation of dopamine. Experimental conditions including molarity, pH, and flow rate of the loading buffer together with a valve switching time have been optimized to provide the highest recovery for dopamine. Experimental setup has been used to determine dopamine in a urine. By using both calibration curve and standard addition method, the dopamine level was determined to be 1.19 and 1.28 mg/L, respectively. Further, we have used experimental design to optimize coupling of two extraction monolithic loops to separation capillary column with monolithic phase for a comprehensive monitoring of dopamine. After multivariate analysis, sample loading flow-rate and a flow-rate of flushing buffer were selected as the most significant variables. Optimized experimental setup was applied to continuously monitor dopamine degradation.
Vývoj metody online extrakce tuhou fází ve spojení s kapalinovou chromatografií založené na polymerních monolitech pro stanovení dopaminu
Keywords: dopamine; monomers; polymer monoliths; solid-phase extraction; dopamin; monomery; polymerní monolity; extrakce tuhou fází